Makna Filosofis Musyawarah Sebagai Bagian Dari Sistem Konstitusi Di Indonesia - Shalahuddin (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
The purpose of this study is to determine the philosophical meaning of deliberation as part of the government system as stated in Article 18 of the 1945 Constitution of the Republic of Indonesia (UUD Negara Republik Indonesia) before the amendment. This research was conducted using a normative juridical research method, with a historical approach and a conceptual approach. With the results of the study, it is explained that Deliberation is a religious command as explained in 3 (three) verses in the Qur'an that contain the command to deliberate, namely: First, Q.S. Al-Baqoroh / 2: 233. Second, Q.S. Ali Imron / 3: 159. Third, Q.S. asy - Syûro/42: 38. Regarding its position in Indonesia from the perspective of a state of law, the command to deliberate has been stated as the basis of the state, namely in Pancasila, namely the fourth principle which reads "The People are Led by the Wisdom of Deliberation/Representation" and in the body of the 1945 Constitution of the Republic of Indonesia it has also been stated in article 18 before the amendment.